A Retrospective Evaluation of Rural Populations: Social and Economic Challenges, Expectations and Evaluation - Yuriy Hubeni; Vitalii Boiko; Petro Olishchuk (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
In 1996 and 2016, respectively, the Independent Creative Group (ICG) conducted a comprehensive sociological study "Economic reform - the eye of the village." The aim of the project was to explore the evaluation of economic reform of rural populations in 5 areas: a) economic reform; b) quality of life and expectations; c) businesses; d) agricultural transformation; e) development of farming. The research was conducted in the form of "sociological fixation" expectations, estimates and other reactions to social challenges. The object of the study was a typical village of the Lviv region. The study confirmed the simultaneous increase of confidence in economic transformation and the growth of pessimism in the impact of reforms. The rural population understands the goals and objectives of reforms, and supports private property and the market economy. The standard of living has improved significantly, but it does not cover the real expectations of the population. Farmers understand the role and importance of entrepreneurship and accept new business entities. The study showed significant structural changes in the views and assessments of rural residents of the Lviv region. There is obvious public awareness of fundamental lifestyle changes in the countryside.